Does hypokalemia contribute to acute kidney injury in chronic laxative abuse? - Eun-Young Lee; Hyaejin Yoon; Joo-Hark Yi; Woon-Yong Jung; Sang-Woong Han; Ho-Jung Kim (The Korean Society of Nephrology, 2015)
Prolonged hypokalemia from chronic laxative abuse is recognized as the cause of chronic tubulointerstitial disease, known as "hypokalemic nephropathy," but it is not clear whether it contributes to acute kidney injury (AKI). A 42-year-old woman with a history of chronic kidney disease as a result of chronic laxative abuse from a purging type of anorexia nervosa (AN-P), developed an anuric AKI requiring hemodialysis and a mild AKI 2 months later. Both episodes of AKI involved severe to moderate hypokalemia (1.2 and 2.7 mmol/L, respectively), volume depletion, and mild rhabdomyolysis. The histologic findings of the first AKI revealed the remnants of acute tubular necrosis with advanced chronic tubulointerstitial nephritis and ischemic glomerular injury. Along with these observations, the intertwined relationship among precipitants of recurrent AKI in AN-P is discussed, and then we postulate a contributory role of hypokalemia involved in the pathophysiology of the renal ischemia-induced AKI.